Interactive Learning Multimedia in Cirebonese Language to Enhance Students Learning Outcome - Ripai, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
This paper discribes the development and validation of interactive multimedia in Cirebonese language learning for the junior high school of the eleventh-grade students. The approach used is research and development. In producing effective and interactive learning media. Ther are three procedural stages : a) identifying the stages; b) developing stage, c) the stage of evaluating and revising. The results of interactive multimedia products are in the form of the Cirebon language learning CD. The results of product validation showed that t, 3,0569E-18 or = 3.0569 x 10-18 smaller than t table at a significance level (α) amounted to 2.034515 0.05, It means it rejects Ho and accepts Ha. It can be concluded that the Cirebonese language learning using developed interactive multimedia is effective in improving students' learning outcome. Therefore, the use of the Cirebon language learning multimedia has a positive influence in improving student learning achievement, so the decision to develop and utilize interactive multimedia for Cirebon language learning is very important to do.